PEMANFAATAN INFORMASI DALAM ARTIKEL ILMIAH: KAJIAN ANALISIS SITIRAN PADA BULETIN PSIKOLOGI UGM - Irianti, Pergola (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2015)
This study aims to determine the utilization of resources in the article of Journal of Psychology UGM period 1993- 2014. The method employed is quantitative, with the subject assessment UGM Psychology Bulletin 1993-2014 period. Object of this study are reference or bibliography of the article that was published in the publication that period. Analysis of data using the percentage method and presented in a frequency table with the aid of a computer program MS Excel. Based on the data analysis, the results show that the name of the faculty with the highest cited frequency is Hastjarjo that is equal to 22,30%, the rank below are Prawitasari amounted to 17,98%, followed by Kuntjoro with a frequency of 12,94%. Then Ancok and Helmi respectively by 8,63%, followed by Hadipranata amounted to 7,91%, and Anwar amounted to 7,19%. The lowest frequency of 0,72% accepted by ten other teaching staff. Utilization of the title work of the teaching staff shows that there are 24 works that have been cited twice or more. The highest frequency of title of the work cited by 16,66% with the title “Reliability and validity” by Saifuddin Anwar, followed by a work entitled “The importance of a paradigm shift and approach to learning and the application of social psychology in Indonesia” by Kuntjoro, and the work entitled “Facial expressions to uncover the basic human emotions “by Prawitasari. Frequency of two titles Kuntjoro works and Prawitasari respectively reached 12,5%. The core information that is used as a source of information is more varied subjective and depends on the needs of authors of the article.